If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=-3(2n-7)
We move all terms to the left:
9-(-3(2n-7))=0
We calculate terms in parentheses: -(-3(2n-7)), so:We get rid of parentheses
-3(2n-7)
We multiply parentheses
-6n+21
Back to the equation:
-(-6n+21)
6n-21+9=0
We add all the numbers together, and all the variables
6n-12=0
We move all terms containing n to the left, all other terms to the right
6n=12
n=12/6
n=2
| Y=5x-125 | | 7^2x-3=93 | | s/10=4 | | 3.953+8.95b=47.65, | | Y=125x-5 | | v/10=3 | | c-19c=-18c | | 5(c+40)=400 | | Y=125x+5 | | d5=−3 | | 5+y+y=57 | | 3/4b−2≤2b+8;b=−4 | | -84=-4(1+5x) | | 10=v/9 | | 4(x+3)=4x+12* | | 70t+35=245 | | 4.2x+6=3x=12 | | -9(5+8d)d=6 | | -1.7-1.6c=-0.42 | | 6x-10=124 | | 7x+21=59.5 | | 3=2t=t | | -4x-19=19-5x | | (2x+10)(2x+20)=216 | | 6t-6=-6t-18 | | f5−20=−24 | | 9.75h+1.00=40 | | -3y+2=-1 | | x/2+3=0.5 | | 1.5{p-4}=14 | | -65-11x=x+139 | | 17+3x=7-2x |